2014
DOI: 10.1038/ismej.2014.37
|View full text |Cite
|
Sign up to set email alerts
|

When the forest dies: the response of forest soil fungi to a bark beetle-induced tree dieback

Abstract: Coniferous forests cover extensive areas of the boreal and temperate zones. Owing to their primary production and C storage, they have an important role in the global carbon balance. Forest disturbances such as forest fires, windthrows or insect pest outbreaks have a substantial effect on the functioning of these ecosystems. Recent decades have seen an increase in the areas affected by disturbances in both North America and Europe, with indications that this increase is due to both local human activity and glo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

23
95
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(121 citation statements)
references
References 56 publications
(44 reference statements)
23
95
3
Order By: Relevance
“…Thus, a shift in ground-dwelling arthropod community structure in response to tree mortality is not surprising given arthropod 326 community sensitivity to changes in vegetation and litter cover from various forest disturbances, ranging from severe wildfires to relatively minor perturbations such as manipulations of coarse 328 woody debris (Ferrenberg et al, 2006; Moretti, Duelli & Obrist, 2006; Lessard et al, 2011; Ober & DeGroote, 2011; Armitage, Ho & Quigg, 2013; Arnan et al, 2014; Delph et al, 2014; 330 Williams et al, 2014; Brunbjerg et al, 2015). Additionally, the shift in arthropod community structure we found here joins recent reports indicating that bark beetle-induced tree mortality 332 alters the structure of soil fungal communities (Treu et al, 2014;Štursová et al, 2014) and nematode community trophic composition (Xiong et al, 2011) of European and North American 334 conifer forests, respectively. Considered collectively, the changes in arthropod communities and understory vegetation structure we found here, and the changes in nematode and fungal 336 communities found in other forests would seem to indicate that tree mortality during insect epidemics can widely affect forest-understory biotic communities.…”
supporting
confidence: 69%
“…Thus, a shift in ground-dwelling arthropod community structure in response to tree mortality is not surprising given arthropod 326 community sensitivity to changes in vegetation and litter cover from various forest disturbances, ranging from severe wildfires to relatively minor perturbations such as manipulations of coarse 328 woody debris (Ferrenberg et al, 2006; Moretti, Duelli & Obrist, 2006; Lessard et al, 2011; Ober & DeGroote, 2011; Armitage, Ho & Quigg, 2013; Arnan et al, 2014; Delph et al, 2014; 330 Williams et al, 2014; Brunbjerg et al, 2015). Additionally, the shift in arthropod community structure we found here joins recent reports indicating that bark beetle-induced tree mortality 332 alters the structure of soil fungal communities (Treu et al, 2014;Štursová et al, 2014) and nematode community trophic composition (Xiong et al, 2011) of European and North American 334 conifer forests, respectively. Considered collectively, the changes in arthropod communities and understory vegetation structure we found here, and the changes in nematode and fungal 336 communities found in other forests would seem to indicate that tree mortality during insect epidemics can widely affect forest-understory biotic communities.…”
supporting
confidence: 69%
“…Increased populations of culturable fungi and Actinobacteria were found in pine forests (Pinus sylvestris L.) defoliated by the pine beauty moth (Panolis flammea D. et S.) and the pine-tree lappet (Dendrolimus pini L.) [6]. In contrast, a bark beetle (Ips typographus L.) induced tree dieback in a spruce (Picea abies L.) forest led to a decrease in the fungal biomass while the bacterial biomass was either unaffected or increased [18,19]. Overall, the effects of the organic input derived by phytophagous insects affecting fungal and bacterial gene abundance are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies investigating the response of bacterial communities after beetle kill reveal a more opaque association. Two studies reported limited changes to soil bacteria after the insect-induced mortality of spruce (10) and limber pines (11), which suggests that these bacterial communities are more resistant to perturbation. However, a subsequent study documented a significant bacterial response coupled with altered edaphic parameters in soils within a forest that was heavily impacted by beetles (ϳ85% mortality) and suggested that there may be a threshold level of mortality necessary to observe a bacterial response within these systems (12).…”
mentioning
confidence: 99%